2012
DOI: 10.1161/hypertensionaha.111.185744
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Renal DJ-1 in the Pathogenesis of Hypertension Associated With Increased Reactive Oxygen Species Production

Abstract: The D2 dopamine receptor (D2R) is important in the pathogenesis of essential hypertension. We have already reported that systemic deletion of the D2R gene in mice results in reactive oxygen species (ROS)-dependent hypertension, suggesting that the D2R has antioxidant effect. However, the mechanism of this effect is unknown. DJ-1 is a protein which has antioxidant properties. D2R and DJ-1 are expressed in the mouse kidney and colocalize and co-imunoprecipitate in mouse renal proximal tubule cells. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 38 publications
(50 reference statements)
4
80
2
1
Order By: Relevance
“…In streptozotocin-treated mice, the Nox2 gene is upregulated in the kidneys. [42][43][44] Taken together, these data indicate that Nox2 may be involved in the development of renal oxidative stress during diabetes and, consequently, in the development of diabetic nephropathy.…”
Section: Nadph Oxidases and Kidney Disease-focus On Nox2 And Nox4mentioning
confidence: 69%
“…In streptozotocin-treated mice, the Nox2 gene is upregulated in the kidneys. [42][43][44] Taken together, these data indicate that Nox2 may be involved in the development of renal oxidative stress during diabetes and, consequently, in the development of diabetic nephropathy.…”
Section: Nadph Oxidases and Kidney Disease-focus On Nox2 And Nox4mentioning
confidence: 69%
“…(selective D 2 R antagonist, Sigma-Aldrich), as previously described (14,15). Differentiated 3T3-L1 adipocytes were transfected with non-silencing siRNA (30 nM, Qiagen) or Drd2 siRNA (30 nM, Qiagen) using Hyperfect (Qiagen) and studied 72 h post-transfection.…”
Section: T3-l1 Cell Culturementioning
confidence: 99%
“…Mouse kidney homogenates and cell lysates were subjected to immunoblotting, as previously described (14,15). The primary antibodies used were rabbit polyclonal anti-D 2 R (Millipore, #AB5084P), rabbit polyclonal antibodies against leptin (ABCAM, #ab9749), IL-6 (ABCAM, #ab6672), adiponectin (ABCAM, #ab22554), visfatin (BioVision, anti-mouse #5908-100), TNFα (ABCAM, #ab9739), OB receptor (Gene-Tex, Inc. GTX25593), and mouse monoclonal anti-GAPDH (glyceraldehyde-3-phosphate dehydrogenase) (Millipore,#MAB374).…”
Section: Immunoblottingmentioning
confidence: 99%
“…3,4 Currently, evidence is emerging that DJ-1 is a multifunctional protein that has potent antioxidant properties and protects kidney against oxidative stress-induced cell injury. 5,6 Interestingly, the content of DJ-1 in glomerular mesangial cells induced by high glucose is relative to time nodes. 7 Studies demonstrated that DJ-1 protein is required for the stabilization of NF-E2-related factor-2 (Nrf2) and subsequent production of Nrf2-regulated enzymes.…”
Section: Introductionmentioning
confidence: 99%